STRATEGI PENGEMBANGAN EKOWISATA AIR TERJUN MANDIN MANGAPAN DI DESA PARAMASAN ATAS KABUPATEN BANJAR PROVENSI KALIMANTAN SELATAN - Camelia Septyanti; Daniel Itta; Rina Muhayah Noor Pitri (Jurnal Sylva Scienteae, 2020)
Paramasan Atas village is a village that has a lot of potential for tourism development. One of the potential ecotourism in Paramasan Atas village is Mandin Mangapan waterfall which has a height of approximately 40 m, clear water, equipped with several showers that come from water sources that can be used for bathing. Besides enjoying the waterfall, the visitors can also enjoy the beauty of the environment around the waterfall surrounded by natural forests or just enjoy the beauty of the waterfall surrounded by natural forests. Lack of endings due to long distances and damaged roads. The purpose of this study was to identify the potential of waterfall ecotourism and analyze the strategy for developing the ecotourism of Mandin Mangapan Waterfall in Paramasan Atas Village, Paramasan District, Banjar Regency. Based on the research results, the ecotourism potential in the Paramasan Atas Village consists of flora diversity (25 species), fauna (15 species), community culture such as "Aruh Adat", tracking 6 km to Mandin Mangapan waterfall within 1-2 hours, natural conditions that are still natural and cool. This location is also used as a place of research and education, based on the results of the SWOT analysis of Mandin Mangapan waterfall in quadrant II, this shows that Mandin Mangapan waterfall is in a favorable position despite facing threats, the strength possessed by Mandin Mangapan waterfall ecotourism can be developed to deal with existing threats. Based on the results of calculations and sorted strategies obtained are Strategy I (S-T) strengths and threats, Strategy II (W-T) weaknesses and threats, Strategy III (S-O) Strengths and opportunities, Strategy IV (W-O) weaknesses and threats.Keywords: Strategy, ecotourism, waterfall, SWOT